2022
DOI: 10.3390/ijms232012644
|View full text |Cite
|
Sign up to set email alerts
|

An Overview into Polyethylene Terephthalate (PET) Hydrolases and Efforts in Tailoring Enzymes for Improved Plastic Degradation

Abstract: Plastic or microplastic pollution is a global threat affecting ecosystems, with the current generation reaching as much as 400 metric tons per/year. Soil ecosystems comprising agricultural lands act as microplastics sinks, though the impact could be unexpectedly more far-reaching. This is troubling as most plastic forms, such as polyethylene terephthalate (PET), formed from polymerized terephthalic acid (TPA) and ethylene glycol (EG) monomers, are non-biodegradable environmental pollutants. The current approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 157 publications
0
12
0
Order By: Relevance
“…The PCA decarboxylation-encoded AroY enzyme for PCA conversion to catechol was inserted into the pKA312 vector. 5 The cat operon genes for catechol-1,2-dioxygenase ( CatA ), muconate cycloisomerase ( CatB ), and muconolactone D isomerase ( CatC ), as well as PcaD , were inserted into the pKE112 vector to generate βKA from catechol through meta-cleavage. 14 For pKE112-catABCpcaD, DNA fragments from each gene were cloned sequentially using EcoRI , KpnI , BamHI , SbfI , and HindIII restriction enzymes.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The PCA decarboxylation-encoded AroY enzyme for PCA conversion to catechol was inserted into the pKA312 vector. 5 The cat operon genes for catechol-1,2-dioxygenase ( CatA ), muconate cycloisomerase ( CatB ), and muconolactone D isomerase ( CatC ), as well as PcaD , were inserted into the pKE112 vector to generate βKA from catechol through meta-cleavage. 14 For pKE112-catABCpcaD, DNA fragments from each gene were cloned sequentially using EcoRI , KpnI , BamHI , SbfI , and HindIII restriction enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…While enzymatic hydrolysis offers a promising biotechnological approach to PET degradation under mild conditions, but it has serious limitations, such as the prerequisite for amorphous or low-crystallinity PET necessary for the proper enzyme activity. 5 Recently, a combination of chemical depolymerization of PET and biological upcycling of TPA have been developed to produce value-added chemicals such as protocatechuic acid (PCA), gallic acid, pyrogallol, catechol, muconic acid, and vanillic acid. These chemicals have various industrial applications and can be produced through whole-cell bioconversion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite a low sequence identity of <50 %, the enzyme structure of Is PETase is rather similar to PET‐hydrolyzing cutinases. Many research groups identified new cutinase‐like (503, [17] 504, [17] 611, [17] Bhr PETase, [18] PET2, [19] PES−H1 (PHL7), [20] MG8 [21] ) and Is PETase‐like (PE−H, [22] Bur PL ( Bb PETase), [23] Rg PETase [24] ) PET hydrolases which expanded the diversity of enzymatic depolymerization of PET [4d–f] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%